2020
DOI: 10.1159/000506533
|View full text |Cite
|
Sign up to set email alerts
|

Renal and Cardiovascular Effects of Sodium Glucose Co-Transporter 2 Inhibitors in Patients with Type 2 Diabetes and Chronic Kidney Disease: Perspectives on the Canagliflozin and Renal Events in Diabetes with Established Nephropathy Clinical Evaluation Trial Results

Abstract: Background: Chronic kidney disease (CKD) risk is elevated in patients with type 2 diabetes mellitus (T2DM). Disease management in these patients has been generally focused on glycemic control and controlling other renal and cardiac risk factors as, historically, few protective therapies have been available. The Canagliflozin and Renal Events in Diabetes with Established Nephropathy Clinical Evaluation ­(CREDENCE) trial of canagliflozin was the first study to demonstrate renal protection with a sodium glucose c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…This initial drop in eGFR was followed by stabilization in eGFR decline compared to placebo from week 3 to the end of the study (-1.85 ± 0.13 vs. -4.59 ± 0.14 ml/ min/1.73 m 2 /year), which is consistent with known renal hemodynamic effects of SGLT2 inhibition [26]. Importantly, as a result of these findings, the FDA issued a new indication for canagliflozin to reduce the risk of ESKD, doubling of serum creatinine, cardiovascular death, and hospitalization for heart failure in adults with T2DM and diabetic nephropathy with albuminuria [ 300 mg/day [27]; this represented the first new indication for the reduction of ESKD risk in 20 years [28,29].…”
Section: Introductionsupporting
confidence: 59%
“…This initial drop in eGFR was followed by stabilization in eGFR decline compared to placebo from week 3 to the end of the study (-1.85 ± 0.13 vs. -4.59 ± 0.14 ml/ min/1.73 m 2 /year), which is consistent with known renal hemodynamic effects of SGLT2 inhibition [26]. Importantly, as a result of these findings, the FDA issued a new indication for canagliflozin to reduce the risk of ESKD, doubling of serum creatinine, cardiovascular death, and hospitalization for heart failure in adults with T2DM and diabetic nephropathy with albuminuria [ 300 mg/day [27]; this represented the first new indication for the reduction of ESKD risk in 20 years [28,29].…”
Section: Introductionsupporting
confidence: 59%
“…SUs were associated with higher mortality only in comparison with DPP-4 inhibitors but not with other drug classes. This finding is surprising as the collective trial evidence so far has demonstrated that DPP-4 inhibitors have neutral effect on mortality and SGLT-2 inhibitors and GLP-1 RAs may have mortality benefit [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…As we pointed out in the introduction, several mechanisms may contribute to the nephroprotective effects seen with canagliflozin [ 3 , 20 ]. Well-known metabolic effects include reduction in glucotoxicity and perivisceral fat.…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of tubuleglomerular balance, providing more sodium to the macula densa, normalizes the tone of the afferent arteriole and is followed by long-term eGFR stabilization and reduction in albuminuria. Finally, reduction in glucotoxicity and proteinuria and the activation of anti-inflammatory and antifibrotic pathways by canagliflozin may play a joint role in reducing tubulointerstitial damage in the diabetic kidney [ 20 ].…”
Section: Discussionmentioning
confidence: 99%